La construction des catégories diagnostiques de maladie mentale - Cédric Brun; Steeves Demazeux; Pierangelo Di Vittorio; François Gonon; Philippe Gorry; Jan Peter Konsman; Fanny Lung; Yannick Lung; Michel Minard; Matthieu Montalban; Nicole Rumeau; Andy Smith (Revue de la Régulation)
Within the framework of a political economy approach, the paper analyses the social construction of both markets and illnesses in the field of mental health, linked with the recent debates associated to the publication of the latter classification of mental disorders (DSM-5). Illustrated by the example of attention deficit and hyperactivity disorder (ADHD), this way of analysing the political work carried out by different actors (pharmaceutical firms, parent of patient associations, the school system, the state, the wealth system, etc.) discerns their respective roles and, in particular, enables research to understand considerable differences between the French and US cases. More than just enlightening ethical questions in the field of mental health, studying the production of scientific discourse about a specific illness identifies the economy of research financing and of scientific publication that drives actor interactions and interdependencies.